Direct transformation of xylan-type hemicelluloses to furfural via SnCl4 catalysts in aqueous and biphasic systems. (May 2015) - Wang, Wenju; Ren, Junli; Li, Huiling; Deng, Aojie; Sun, Runcang
Graphical abstract: Highlights: An efficient process was developed for the transformation of xylan to furfural. SnCl4 was found to be an effective catalyst. The bio-based 2-MTHF/H2 O biphasic system exhibited superior furfural selectivity. 78.1% furfural yield was achieved from beech xylan at 150 °C for 120 min. Furfural yield to some extent was determined by the chemical and structure of hemicelluloses. Abstract: Direct catalytic transformation of xylan-type hemicelluloses to furfural in the aqueous system and the biphasic system were comparatively investigated under mild conditions. Screening of several promising chlorides for conversion of beech xylan in the aqueous system revealed the Lewis acid SnCl4 was the most effective catalyst. Comparing to the single aqueous system, the bio-based 2-methyltetrahydrofuran (2-MTHF)/H2 O biphasic system was more conducive to the synthesis of furfural, in which the highest furfural yield of 78.1% was achieved by using SnCl4 as catalysts under the optimized reaction conditions (150 °C, 120 min). Additionally, the influences of xylan-type hemicelluloses with different chemical and structural features from beech, corncob and bagasse on the furfural production were studied. It was found that furfural yield to some extent was determined by the xylose content in hemicelluloses and also had relationships with the molecular weight of hemicelluloses and the degree of crystallization.